Segmental and transmural motion of the rat myocardium estimated using quantitative ultrasound with new strategies for infarct detection - Wang, Yinong; Chen, Wufan; Wang, Qing (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: The estimation of myocardial motion abnormalities is of great potential in early diagnosis of myocardial infarction (MI). This study aims to quantitatively analyze the segmental and transmural myocardial motion in MI rats incorporating with two novel strategies of algorithm parameter optimization and transmural motion index (TMI) calculation. Methods: Twenty-one rats were randomly divided into 3 groups (n=7 per group): Sham, MI and ischemia-reperfusion (IR) group. Ultrasound radio-frequency (RF) signal was acquired from each rat heart 1 day and 28 days post animal model establishment, thus total 6 datasets were represented as Sham1, Sham28, MI1, MI28, IR1 and IR28. The systolic cumulative displacement was calculated using our previously proposed vectorized normalized cross-correlation (VNCC) method. A semiautomatic regional and layer-specific myocardium segmentation framework was proposed for transmural and segmental myocardial motion estimation. Two novel strategies were proposed, the displacement compensated cross correlation coefficient (DCCCC) for algorithm parameter optimization and the transmural motion index (TMI) for quantitative estimation of the cross-wall transmural motion gradient. Results: The results showed that an overlap value of 80% used in VNCC guaranteed a more accurate displacement calculation. Compared to the Sham1 group, the systolic myocardial motion reductions were significantly detected (p<0.05) in the middle anteroseptal (M-ANT-SEP), basal anteroseptal (B-ANT-SEP), apical lateral (A-LAT), middle inferolateral (M-INF-LAT) and basal inferolateral (B-INF-LAT) wall as well as a significant TMI drop (p<0.05) in M-ANT-SEP wall in the MI1 rats, significant motion reductions (p<0.05) also appears in the B-ANT-SEP and A-LAT wall in the IR1 group. The motion improvements (p<0.05) were detected in the M-INF-LAT wall from the MI28 group and the A-SEP wall in the IR28 group compared to the MI1 and IR1 groups, respectively. Discussion: Our results show that by the use of our method the MI-induced reductions and reperfusion-induced recovery in systolic myocardial contractility could be successfully evaluated and most post-MI myocardial segments could recover systolic function at various extents in remodeling phase. In conclusion, the ultrasound-based quantitative estimation framework for estimating segmental and transmural motion of myocardium proposed in our study is of great potential in non-invasive, novel and early MI detection.